The association between dietary branched-chain amino acids and the risk of cardiovascular diseases in Chinese patients with type 2 diabetes: A hospital-based case–control study - Zheng, Lu; Cai, Jun; Feng, Yong-hui; Su, Xin; Chen, Shi-yun; Liu, Jia-zi; Li, Wan-lin; Ouyang, Rui-qing; Ma, Jun-rong; Cheng, Chen; Mu, Ying-jun; Zhang, Shi-wen; et al. (Frontiers in Nutrition, 2022)
Background Previous studies showed conflicting evidence on the association between the intake of dietary branched-chain amino acid (BCAA) and the risk of cardiovascular disease (CVD). However, this relationship has not been studied in patients with type 2 diabetes. Therefore, we evaluated the effects of total and individual dietary BCAA (leucine, isoleucine, and valine) intake on CVD risk among individuals with type 2 diabetes in China. Materials and methods A total of 419 patients with type 2 diabetes who have been diagnosed with CVD (within 2 weeks) were recruited between March 2013 and September 2015 in China. Cases with CVD were 1:1 matched to controls with type 2 diabetes but without CVD by age (±5 years) and sex. A validated 79-item semiquantitative food frequency questionnaire (FFQ) was administered to assess the participants' dietary data. Total dietary BCAA per individual was the summation of the daily intake of isoleucine, leucine, and valine. OR and corresponding CIs were computed by conditional logistic regression models adjusted for potential confounders. Results Median values of the daily intake of total BCAA were 11.87 g, with an interquartile range of 10.46–13.15 g for cases, and 12.47 g, with an interquartile range of 11.08–13.79 g for controls (P = 0.001). Dietary BCAA was inversely related to CVD risk after multivariable adjustment (OR Q4−Q1 = 0.23, 95%CI = 0.10, 0.51, P trend <0.001 for total BCAA; OR Q4−Q1 = 0.20, 95%CI = 0.07, 0.53, P trend = 0.001 for leucine). For each 1-S.D. increase in total dietary BCAA, leucine or valine intake was associated with 54% (95%CI = 29%, 70%, P = 0.001), 64% (95%CI = 29%, 82%, P = 0.003), or 54% (95%CI = 1%, 79%, P = 0.049) decrease in the risk of CVD, respectively. Whole grains, starchy vegetables, mushrooms, fruit, eggs, and dairy and dairy product-derived BCAA were found to attenuate CVD risk (P ranged: = 0.002–0.027). Conclusion Higher BCAA intake, in particular leucine and valine, might be associated with a lower risk of CVD.